2020
DOI: 10.14814/phy2.14578
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and gustatory dysfunction in COVID‐19 patients: A meta‐analysis study

Abstract: COVID‐19, caused by a novel coronavirus, is a persistent global pandemic. It is crucial to examine existing reports to effectively summarize and characterize its clinical course. We used a large‐scale meta‐analysis to establish prevalence rates for loss of olfaction and gustation in COVID‐19 positive patients. PubMed/Medline, Embase, and Web of Sciences were searched for articles published until April 30, 2020. Furthermore, to avoid missing papers, more searches were carried out in the reference lists of cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 34 publications
4
37
0
1
Order By: Relevance
“…For example, Hajikhani et al analyzed 3739 patients from 15 studies with PCR-confirmed COVID-19. 17 The taste and smell impairment rates were 49% and 61%, respectively. Among patients hospitalized in the ICU, we found that 42.3% (n ¼ 22/52) experienced taste and/or smell impairment, consistent with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Hajikhani et al analyzed 3739 patients from 15 studies with PCR-confirmed COVID-19. 17 The taste and smell impairment rates were 49% and 61%, respectively. Among patients hospitalized in the ICU, we found that 42.3% (n ¼ 22/52) experienced taste and/or smell impairment, consistent with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the proportion of patients experiencing chemosensory dysfunction was relatively high. According to a metanalysis by Hajikhani et al, 34 at presentation, the estimated rate of taste disorders was 49.0% and of olfactory disorders was 61.0%. Data regarding the short-term recovery from these symptoms are divergent.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, evidence has accumulated showing that two atypical symptoms, the loss of taste and/or loss of smell, may be frequently triggered by SARS-CoV-2 infection [7]. This is supported by some recent meta-analyses, such as those published by Hajikhani et al [8], as well as by Tong and colleagues [9], who reported that olfactory and gustatory dysfunctions are present in over 50% of patients with SARS-CoV-2 infection. Notably, the recent meta-analysis of Hoang et al also revealed that olfactory and/or gustatory dysfunctions might also be highly specific symptoms of SARS-CoV-2 infection, since they were found to be 10-fold more likely to occur in COVID-19 patients as opposed to those with other acute respiratory infections (odds ratio, 11.3; 95% confidence interval [95% CI], 5.4-23.4) [10].…”
Section: Introductionmentioning
confidence: 85%